The effect of service quality and satisfaction on customer loyalty at Kumon East Jakarta - Nikmah, Wasilatun; Armaniah, Henny (Journal of Economics and Business Letters, 2021)
This study aims to determine Service Quality and Satisfaction Customer Loyalty at the Kumon Seulawah Raya Jaatiwaringin Course - East Jakarta. The population in this study were all customers of the Kumon Seulawah Raya Jatiwaringin course. Researchers used the accidental sampling method with a sample of 83 people from the population of Kumon Seulawah Raya Jatiwaringin Course Customers. Instrument testing in this study uses validity and reliability tests, while the analytical method used is multiple linear regression with t- test and F test and coefficient of determination (R2) test. In this study, an analysis was carried out using the SPSS for windows version 24.0 computer application. Based on the regression analysis, the model (regression equation) formed is Y = 1.760 + 0.166X1 + 0.361X2. The results of the analysis on the t -test, the Service Quality variable (X1) shows the results of the t-count value of 3.011 > t-table of 1.990 and a significant value of 0.003 <0.05 then Ho1 is rejected and Ha1 is accepted, meaning that there is a positive and partially significant effect between Quality Service with Customer Loyalty. While the Customer Satisfaction variable (X2) shows the results of the t-count value of 4.712 > t-table of 1.990 and a significant value of 0.000 <0.05 then Ho2 is rejected and Ha2 is accepted, meaning that there is a positive and partially significant effect between Customer Satisfaction and Customer Loyalty Kumon Seulawah Raya Jatiwaringin. In the results of the F test analysis, the value of F-count is 20.144 > Ftable is 3.11 with a significant level of 0.000 <0.05, then Ha is accepted. So that it can be said that the service quality variable (X1) and the customer satisfaction variable (X2) has a positive and significant effect on customer loyalty (Y). The results of the analysis of determination (R2) are known that the value of R Square is 0.335. This shows that 33.5% of the independent variables consisting of Service Quality and Customer Satisfaction affect the dependent variable, namely Customer Loyalty. The remaining 66.5% is influenced by other variables not examined.